Immunosuppressive Mesenchymal Stromal Cells Derived from Human-Induced Pluripotent Stem Cells Induce Human Regulatory T Cells In Vitro and In Vivo - Roux, Clémence; Saviane, Gaëlle; Pini, Jonathan; Belaïd, Nourhène; Dhib, Gihen; Voha, Christine; Ibáñez, Lidia; Boutin, Antoine; Mazure, Nathalie M.; Wakkach, Abdelilah; Blin-Wakkach, Claudine; Rouleau, Matthieu (Frontiers in Immunology, 2018)
Despite mesenchymal stromal cells (MSCs) are considered as a promising source of cells to modulate immune functions on cells from innate and adaptive immune systems, their clinical use remains restricted (few number, limited in vitro expansion, absence of a full phenotypic characterization, few insights on their in vivo fate). Standardized MSCs derived in vitro from human Induced Pluripotent Stem (huIPS) cells, remediating part of these issues, are considered as well as a valuable tool for therapeutic approaches, but their functions remained to be fully characterized. We generated multipotent MSCs derived from huiPS cells (huiPS-MSCs), and focusing on their immunosuppressive activity, we showed that human T cell activation in co-culture with huiPS-MSCs was significantly reduced. We also observed the generation of functional CD4+ FoxP3+ regulatory T cells. Further tested in vivo in a model of human T cell expansion in immune-deficient NSG mice, huiPS-MSCs immunosuppressive activity prevented the circulation and the accumulation of activated human T cells. Intra-cytoplasmic labelling of cytokines produced by the recovered T cells showed reduced percentages of human differentiated T cells producing Th1 inflammatory cytokines. In contrast, T cells producing IL-10 and FoxP3+-regulatory T cells, absent in non-treated animals were detected in huiPS-MSCs treated mice. For the first time, these results highlight the immunosuppressive activity of the huiPS-MSCs on human T cell stimulation with a concomitant generation of human regulatory T cells in vivo. They may favor the development of new tools and strategies based on the use of huiPS cells and their derivatives for the induction of immune tolerance.